Environmental Deterioration In Tafsir Maqasidi: A Comparative Study Of Tafsir Al-Munir And Al-Azhar - Diningrum, Melinda Retno; Nurrohim, Ahmad; Yaqin, Iqbal Nurul (ZAD Al-Mufassirin, 2024)
Environmental degradation represents a significant challenge that affects the ecological, social, and spiritual aspects of humanity. This study focuses on how maqasidi tafsir can be employed to understand and address environmental issues, by analysing Tafsir Al-Munir by Wahbah al-Zuhaili and Tafsir Al-Azhar by Buya Hamka. Both tafsirs emphasise human responsibility towards nature as a trust from Allah, albeit with different approaches. Tafsir Al-Munir places greater emphasis on the application of Islamic law in environmental management, whereas Tafsir Al-Azhar highlights ethical, spiritual aspects and the harmony of nature. The main finding of this study demonstrates that maqasidi tafsir offers a comprehensive perspective by integrating legal, moral, and spiritual dimensions in environmental preservation. This comparative tafsir study contributes to contemporary environmental ethics by illustrating how the principles of Islamic law can provide solutions to modern ecological challenges, linking legal frameworks with moral values to maintain environmental balance and sustainability.